Glaucoma Patients' Trust in the Physician - Kelly W. Muir; Cecilia Santiago-Turla; Sandra S. Stinnett; Leon W. Herndon; R. Rand Allingham; Pratap Challa; Paul P. Lee (Journal of Ophthalmology)
Objectives. To describe glaucoma patients' trust in the physician and to test the hypothesis that increased interpersonal trust is associated with increased medication adherence. Methods. One hundred ninety-five subjects with open-angle glaucoma seen by multiple glaucoma subspecialists participated in a cross-sectional patient survey and concomitant chart review which included a test of health literacy and the Trust in Physician Scale (TPS), a scale from 1–100, with 100 indicating greatest trust. Charts were reviewed for visual acuity and visual field results. Subjects' pharmacies were contacted to ascertain medication refill rates over the preceding six months. Results. TPS scores ranged from 57.5 to 100, 78.7±8.4 (mean±SD,) median 75.0. When age, race, gender, baseline visual acuity and visual field status, education level, and literacy status were considered, only race was associated with TPS. Caucasians expressed slightly higher levels of trust (n=108; TPS 80.1±8.2) than non-Caucasians, (n=87 (82 Africans Americans); TPS 77.1±8.4; P=.012). TPS score was not associated with refill rates (P=.190). Conclusions. Trust in physician is generally high in this group of glaucoma patients but varies slightly by race. Trust in physician was not associated with glaucoma medication adherence in this tertiary care population.